Analysis of the Influence of Political Power on the Implementation of the Islamic Economic System - Suud Sarim Karimullah (Jurnal Ekonomi Syariah, Akuntansi dan Perbankan (JESKaPe), 2024)
This study aims to analyze how political power affects the implementation of Islamic economic principles and identify what political factors accelerate or hinder the implementation of the Islamic financial system. This study uses the library research method because the primary data is obtained from relevant literature sources with an integrative and connective approach. The results suggest that political power is a significant determinant and a stumbling block for Islamic economics to move beyond mere rhetoric and achieve substantial implementation. On the one hand, political support can create regulations that strengthen Islamic banks, Islamic insurance, and ethical capital markets. However, the irony arises when broader political interests force Islamic economic principles to compromise with global capitalism's interest and speculation-laden currents. In a system often dictated by conventional economic forces, key instruments such as zakat and waqf are usually left ineffective. At the same time, prohibitions on riba and gharar are frequently pushed rather than enforced. Without political courage to challenge capitalist domination and commit to structural transformation, Islamic economics will only be a beautiful slogan but weak in the face of modern economic pragmatism.